2018
DOI: 10.1038/s41598-017-18955-x
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Enhancement During Water and Hydrocarbon Condensation on Lubricant Infused Surfaces

Abstract: Vapor condensation is routinely used as an effective means of transferring heat or separating fluids. Dropwise condensation, where discrete droplets form on the condenser surface, offers a potential improvement in heat transfer of up to an order of magnitude compared to filmwise condensation, where a liquid film covers the surface. Low surface tension fluid condensates such as hydrocarbons pose a unique challenge since typical hydrophobic condenser coatings used to promote dropwise condensation of water often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
137
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(137 citation statements)
references
References 53 publications
(47 reference statements)
0
137
0
Order By: Relevance
“…Slippery liquid-infused porous surfaces (SLIPS) exhibit remarkable properties such as ultra-low contact angle hysteresis (CAH) for a wide variety of liquids 1 , 2 , excellent self-healing capability 2 , 3 , and stability under high pressures or temperatures 2 , 4 , 5 . In addition to repelling liquids, SLIPS have been shown to promote anti-fouling 6 13 , self-cleaning 1 , 2 , 14 , anti-icing 15 20 , reduced drag 21 24 and enhanced phase-change heat transfer 25 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Slippery liquid-infused porous surfaces (SLIPS) exhibit remarkable properties such as ultra-low contact angle hysteresis (CAH) for a wide variety of liquids 1 , 2 , excellent self-healing capability 2 , 3 , and stability under high pressures or temperatures 2 , 4 , 5 . In addition to repelling liquids, SLIPS have been shown to promote anti-fouling 6 13 , self-cleaning 1 , 2 , 14 , anti-icing 15 20 , reduced drag 21 24 and enhanced phase-change heat transfer 25 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Lately, Preston et al [139] experimented with the condensation of water and toluene and found that htc was 4.5 times higher with the implementation of LIS. Nevertheless, they noticed that with the passage of time, condensation mode changes from DWC to FWC due to lubricant depletion.…”
Section: Lubricant-infused Surfaces (Lis)mentioning
confidence: 99%
“…In addition, the presence of water and detergents accelerates the degradation process 57 . Although some reports examine the effect of washing on the printed electrodes' behavior, more research is needed to fully understand the impact of the electrode shape and material on the phenomena occurring during washing [58][59][60][61][62] .…”
Section: Introductionmentioning
confidence: 99%